Demographic ageing and public debt in Poland. Is the public finance sector about to collapse? - Marek Piotrowski; Magdalena Antoń; Emilia Kwiatkowska (Entrepreneurship and Sustainability Issues)
The paper addresses the issue of demographic ageing of the Polish population, with particular emphasis on its impact on the functioning of the national economy. Its main objective was to assess the influence of demographic changes on the public finance sector in Poland. To achieve the main objective of assessing the impact of demographic aging on Poland's public finance sector, a study of correlation and periodic change dynamics was conducted, covering the period from 2000 to 2022. Additionally, a regression analysis was performed using the Classical Least Squares Method. In the research part of the paper, changes in the age structure in Poland are characterized, and the impact of this phenomenon on the economic situation of elderly persons is assessed. Using an econometric model, the impact of factors related to demographic changes, such as natural population growth and the demographic dependency ratio on the post-working-age population, on the value of the state's public debt was assessed. Based on the model, an attempt was made to forecast this variable for the years 2023-2026. The analyses revealed that the consequences of demographic ageing threaten the stability of the public finance sector. The study showed that with a 95% probability, a decrease in natural population growth by 1000 individuals leads to an increase in debt by 0.81 billion PLN, and an increase in the demographic dependency ratio on the post-working-age population results in an increase in public debt by 19.71 billion PLN, with other conditions unchanged. Furthermore, the prediction confirmed that, under the conditions of the values of explanatory variables forecasted by the Central Statistical Office, its value in 2026 will increase by 0.38% compared to 2022.